The first person pronoun in archaic Chinese, with a note on duplex characters - Benedict, Paul K. (2024)
Tibeto-Burman (TB) *nga (tone *A) `first person pronoun' and the topic marker (TM) *ga - ka play a strange "cat and mouse" game as they romp about the family. The widely represented *nga, from Chepang, Chang (Northern Naga), and Trung (Nungish) on the north(/west) and Tujia (west-central China) on the east to Burmese-Lolo on the south(/east), as our "mouse," is at times firmly in the paws of our TM "cat": Waling (Kiranti) angka < *-nga-ga '1 p. prn.' TB *na(:)ng '2 p. pm' largely escaped this fate, indicating that in TB-land, even as in Washington, the Ego was by far one's favorite topic! In the monosyllabizing TB family, a *nga-ga or *nga-ka is unstable, especially for a pronominal, with the result that in Lepcha and Ahi Lolo our "cat" ate our "mouse": both go < *ga '1 p. prn.' , with parallel developments in Qiangic as well as Kuki-Naga. Finally, in Written Tibetan (WT) the -ga -ka TM is directly suffixed, whereas in Written Burmese (WB) it reflects an intervening ergative *-s: WB -ka' < *s-ga, with regular 'creaky voice' [represented as '] < *s-; cf. WT sga, WB ka' `saddle'.